DETERMINATION OF PASSENGER CARS EQUIVALENCE (PCE) USING LINEAR REGRESSION ANALYSIS METHOD (THE CASE STUDY IS THE ROAD OFAHMAD YANIAND PB. SUDIRMAN STREET, JEMBER) - Putri, Nara Maika; Hasanuddin, Akhmad; Sulistyono, Sonya (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Passenger car equivalence (PCE) is the conversion factor of various types of vehicles to become passenger cars. Passenger car equivalence function is to make uniform heterogeneous traffic flow into homogeneous traffic flow. The value of passenger car equivalence of each type of vehicle is different in each size, because every road has different traffic characteristics and geometric condition. This study was conducted in order to get the appropriate value of passenger car equivalence in the research area. The researcher colleted the data of traffic volume and the road’s geometry using Primer survey. The analysis method that is used to get the value of passenger car equivalence is multiple linier regression analysis. The finding values of passenger car equivalence in the PB. Sudirman street (2/2 UD) are MC = 0,32 and HV=2,31, the Ahmad Yani street (3/1) are MC= 0,34 and HV= 1,3. While, based on MKJI 1997 the passenger car equivalence values of PB. Sudirman street are MC=0,4 and HV = 1.3, andthe Ahmad Yani street are MC = 0.25 and HV = 1.3.So, the different values of passenger car equivalence in Sudirman Street are with rasio 11% for MC and 28% for HV. While, in Ahmad Yanistreet the different values are with rasio 14% for MC and 37% for HV. So that, in morning peak hours the value of DS regression in BP sudirman is smaller than MKJI and the difference is 7%. while in Ahmad Yani street, the value of DS regression is bigger than MKJI and the diference is 9%.